Monocyte and macrophage profiles in patients with inherited long-chain fatty acid oxidation disorders - Verberk, Sanne G.S.; Hahn, Nico; Heister, Daan; Haverkamp, Jorien; Snelder, Khya S.; de Goede, Kyra E.; Gorki, Friederieke S.; Hendriks, Jerome J.A.; Houtkooper, Riekelt H.; Visser, Gepke; Sjouke, Barbara; Langeveld, Mirjam; et al. (Biochimica et biophysica acta. Molecular basis of disease, 2025)
Patients with inherited disorders of the long-chain fatty acid oxidation (lcFAO) machinery present with a heterogeneous profile of disease manifestations and aggravation of symptoms is often triggered by inflammatory activation. Monocytes and macrophages are innate immune cells that play a major role in the onset and resolution of inflammation. These cells undergo metabolic rewiring upon activation including the regulation of the FAO rate. The rewiring of FAO and the effect of lcFAO disorders (lcFAOD) on human monocyte and macrophage phenotype and function remain largely unknown. Here, we performed extensive phenotyping of circulating monocytes and analyzed plasma cytokine levels in 11 lcFAOD patients and 11 matched control subjects. In patients with lcFAOD, we observed induced plasma levels of the inflammatory cytokines IL-1β and IL-6, and enhanced CD206 and CD62L surface marker expression in circulating monocyte subsets. To mimic the most common lcFAOD very-long-chain acyl-CoA dehydrogenase disorder (VLCADD), we used siRNA-mediated knockdown of the ACADVL gene (encoding VLCAD) in macrophages derived from healthy volunteers. Hereby, we found that siVLCAD affected IL-4-induced alternative macrophage activation while leaving LPS responses and cellular metabolism intact. In the same line, monocyte-derived macrophages from lcFAOD patients had elevated levels of the IL-4-induced alternative macrophage markers CD206 and CD200R. Still, they did not show major metabolic defects or changes in the LPS-induced inflammatory response. Our results indicate that monocytes and macrophages from lcFAOD patients present no major inflammatory or metabolic differences and show that IL-4-induced surface markers are intertwined with lcFAO in human macrophages. [Display omitted] •Patients with long-chain fatty acid oxidation disorders (lcFAOD) show slightly elevated circulating IL-1β and IL-6 cytokine levels•Inflammatory responses to lipopolysaccharide (LPS) areunchanged in lcFAOD leukocytes•CD206 surface expression is elevated in monocytes and in IL-4-activated lcFAOD macrophages•lcFAOD macrophages display similar metabolic phenotypes compared to healthy control macrophages.